Pengaruh Penambahan Dynamic Neuromuscular Stabilization setelah diberikan Transcutaneus Electrical Nerve Stimulation terhadap nyeri pada kasus Low Back Pain Myogenic - Febriana, Dwi Margasari, Agus Widodo, S.Fis.,Ftr., M.Fis, Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes (2015)
Background: Low back pain is the myogenic lower back pain caused by disorders or musculoskeletal disorders accompanied by neurological disorders between vertebrae thorax 12 to the bottom of the hip or anus. Objective: This study was to determine the effect of transcutaneous electrical nerve stimulation for pain myogenic LBP cases and determine the effect of Dynamic Neuromuscular Stabilization after transcutaneous electrical nerve stimulation given to pain in the case of myogenic LBP. Methods: This study used a quasi-experimental methods are often referred to as a quasi-experimental approach to pre-test and post-test two design groups. In this study the author uses primary data is by taking the data before and after the intervention. The subjects of the research were used in this study is less than 30 subjects, so that it can be assumed that the data is not normally distributed, the non-parametric test. Test the effect on each group is used to determine the results before and after therapy. Test two groups of pairs of pre and post, then the analysis of the data used is Wilcoxon test. Results: Obtained p-value: 0.038 or p <0,05 so that Ho refused and Ha accepted, which means no influence. Whereas in the treatment group obtained p value: 0.039 or p <0,05 so that Ho refused and Ha accepted, which means there is the effect of TENS on pain in low back pain myogenic. Conclusion: there is the effect of adding Dynamic Stabilization Neuromuscular after transcutaneous electrical stimulation given to the reduction of pain in cases of low back pain myogenic.